Giant autovenous shunt aneurysm, hybrid treatment approach - L. N. Ilina; D. M. Galyautdinov; V. P. Vasilyev; E. V. Dzybinskaya; E. E. Vlasova; S. K. Kurbanov; E. V. Merkulov; I. S. Fedotenkov; E. V. Kurilina; A. A. Shiryaev; R. S. Akchurin (Российский кардиологический журнал)
.